2021
DOI: 10.1101/2021.04.05.437619
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perseverative behavior under uncertainty is enhanced by tryptophan depletion but diminished with subclinical obsessive–compulsive symptoms

Abstract: Serotonin is critically involved in flexible decision-making, yet the preponderance of evidence comes from non-human studies. Many insights about the serotonin's function have come from the technique of dietary acute tryptophan depletion (ATD). However, it is unclear whether ATD modulates choice behavior during probabilistic reversal learning (PRL), a widely used model of behavioral flexibility with significant translational and clinical value. To determine whether ATD affects latent choice tendencies, we appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 82 publications
1
10
0
Order By: Relevance
“…In the exact model, the choice hysteresis parameter was significantly different from 0: 1.06±0.05, t(391)=21.8, p<0.0001 and was negatively associated with OCI-R total score in line with previous studies 7,14,15,17 : 𝛽𝛽 𝑂𝑂𝑂𝑂𝑂𝑂𝑅𝑅 𝑡𝑡𝑡𝑡𝑡𝑡𝑡𝑡𝑡𝑡 = −0.17 (𝑆𝑆𝑆𝑆 = 0.05), 𝑝𝑝 = 0.0007 (controlling for the covariates:…”
Section: Learning Imprecisions Are Sufficient To Account For Choice Hysteresissupporting
confidence: 83%
See 3 more Smart Citations
“…In the exact model, the choice hysteresis parameter was significantly different from 0: 1.06±0.05, t(391)=21.8, p<0.0001 and was negatively associated with OCI-R total score in line with previous studies 7,14,15,17 : 𝛽𝛽 𝑂𝑂𝑂𝑂𝑂𝑂𝑅𝑅 𝑡𝑡𝑡𝑡𝑡𝑡𝑡𝑡𝑡𝑡 = −0.17 (𝑆𝑆𝑆𝑆 = 0.05), 𝑝𝑝 = 0.0007 (controlling for the covariates:…”
Section: Learning Imprecisions Are Sufficient To Account For Choice Hysteresissupporting
confidence: 83%
“…A tendency to repeat previous choices irrespective of their value has been traditionally captured with an additional parameter during choice [47][48][49] . This "choice hysteresis" (tendency to repeat same action) parameter has previously been linked to compulsivity 7,14,15,17 . However, we found that choice hysteresis was no longer necessary when accounting for learning imprecisions, aligned with previous simulations 24 (Supplementary Information).…”
Section: Learning Imprecisions Are Sufficient To Account For Choice Hysteresismentioning
confidence: 94%
See 2 more Smart Citations
“…Several studies have related serotonin, OCD, and obsessive-compulsive symptoms to stimulus stickiness [72][73][74][75] . Those studies used reversal-learning tasks, but analyzed behavior with S-R-learning models without state inference 73,75 . Our findings, like prior ones 69,70 , show that participants perform state inference in these tasks.…”
Section: Discussionmentioning
confidence: 99%

Serotonin Reduces Belief Stickiness

Conceição,
Petzschner,
Cole
et al. 2023
Preprint